Resources and Cooperation in Integrated Emergency Management Systems in Disaster Management - Berton Suar Pelita Panjaitan (Institute of Computer Science (IOCS), 2022)
Preparedness is an effort carried out to anticipate the possibility of a disaster in an area, this action is taken to avoid the loss of life, loss of property, and changes in the life of the community. Preparedness to face a disaster is a condition of individuals and groups who have physical and psychological abilities in dealing with disasters. The government's role in responding to disaster relief efforts is carried out through several regional policies and regulations with the support of several community organizations, companies, private institutions and institutions, the military, and other community organizations. The regulatory framework that has been issued by the government seeks to respond to various disaster events in Indonesia by building a disaster management system in terms of legislation, institutions, implementation (pre, emergency response, and post-disaster). which is relevant to the focus of the research that the researcher is looking for, namely resources and cooperation in the emergency response system in disaster management, while the results of this study explain that community empowerment in an effort to deal with emergency cases is an effort to increase the effectiveness of the integrated emergency service system, especially to deal with natural and non-natural disasters. Through the provision of education and training as first aid materials, both formally and informally delivered and carried out regularly and continuously, it is hoped that the community will be able to know the various efforts and countermeasures in the context of dealing with disasters appropriately. Disaster preparedness policy is very important and is a concrete effort issued by the government and several related parties, especially in carrying out disaster preparedness activities. The policy also affects the disaster warning system, resource mobilization, funding, management organization, and important facilities for disaster emergencies.